Pengaruh Ongkos Kirim dan Harga terhadap Perilaku Konsumen dalam Melakukan Pembelian Ulang pada Marketplace Shopee - Rukun Santoso; Alfi Fuadah; Rivaldo Kurniawan Iryanto; Nurul Aini; Sahara Sahara (Jurnal Simki Economic, 2023)
This study aims to determine the effect of price and service quality on consumer behaviour in determining repurchase intentions on the Shopee marketplace through the variable shipping cost as an intervening factor. The data taken is customer data or Shopee visitors in Indonesia during 2020, totalling 126 million visitors, and data analysis using path analysis through the PLS 3.0 program. The research method used is a quantitative descriptive research method using data analysis. The study results concluded that the price and service quality variables influence consumer behaviour variables to determine repurchase intentions in the marketplace on the Shopee platform. Simultaneously the price and service quality variables affect the consumer behaviour variable to determine repurchase intention through the shipping cost variable as an intervening factor. The study results show that online buying and selling platforms such as Shopee always set prices according to consumer expectations. They are improving service to have a qualified quality through service improvement and determining consistent shipping costs so that customers will make repeat purchases.